Improving the Diagnosis of Post-traumatic Stress Disorder and Anxiety-depressive Disorders Using the Methods of Phenomenological Philosophy: Experience of Interdisciplinary Practices in Ukraine - Rudenko, Sergii; Tasenko, Mykhailo (Studia Warmińskie, 2024)
The article discusses the potential advantages of using phenomenological psychopathology methods to improve the diagnosis of post-traumatic stress disorder (PTSD) and anxiety-depressive disorders, especially in the context of the ongoing war in Ukraine. It highlights the limitations of relying solely on the diagnostic criteria set out in International statistical classification of diseases and related health problems, 10th revision (ICD-10), arguing that they may not reflect the subjective, lived experience of mental disorders. The authors note a significant increase in the number of diagnosed mental and behavioural disorders in Ukraine since the Russian invasion. The number of cases of PTSD has quadrupled compared to pre-war levels. Common triggers include fear, anxiety, witnessing violence, personal harm, loss of loved ones, isolation, and displacement. The study used analytical, comparative, and interdisciplinary methods to explore how the approaches of phenomenological philosophy and phenomenological psychopathology can complement traditional psychiatric interviewing. Phenomenological psychopathology is an interdisciplinary field that aims to study changes in dimensions such as lived time, space, body, and self that manifest in mental illness. The main methods include semi-structured phenomenological interviews that allow patients to describe their subjective experiences. The authors argue that the combination of phenomenological methods with standard psychiatric diagnostic methods in Ukraine will allow for a more complete and accurate diagnosis of PTSD, anxiety, depression, and other conditions exacerbated by the war. This interdisciplinary, patient-centred approach promises to improve the quality of mental health care as the country recovers. However, they acknowledge that the application of these methods in Ukraine is currently fragmented. The authors suggest that the methods of phenomenological psychopathology are a valuable but underutilised tool for addressing the challenges facing the mental health system in Ukraine.